Creative management strategies to build business appeal - Maulidiana, Ade Ega; Prajawati, Maretha Ika (Maliki Interdisciplinary Journal, 2025)
Creative management plays a central role in building business appeal at Cafe Istana Pengangguran, a grape-garden-based cafe located in Pakis District, Malang Regency. The transformation of the vineyard into a three-story cafe with a rooftop reflects the application of creativity, innovative behavior, and adaptive capabilities in responding to market dynamics. Through direct observation, this research assesses how creative spatial design, interactive visitor experiences, and a natural atmosphere are utilized to enhance comfort and interest. The findings indicate that the integration of agritourism, educational elements, and culinary services creates new value that strengthens the cafe's business identity. These efforts align with the concepts of Innovative Work Behavior and Dynamic Capabilities, emphasizing the importance of innovation and adaptability for MSMEs. Recommendations include developing grape-themed educational programs, enhancing visual-based digital promotion, and collaborating with local MSMEs to enrich visitor experiences. The creative strategies implemented help position the cafe as a competitive culinary and agro-tourism destination in Malang.